In situ beta‐gamma separation algorithm for cost‐effective assessment of radioactive waste resources - Bae, Jun Woo; Kim, Hee Reyoung (International journal of energy research, 2018)
Summary A method for discriminating between the counting rates attributable to beta rays and gamma rays was proposed. The method was based on the characterization of the sensitivity ratios of multiple scintillators. Four scintillators were used in this study: 10 and 20‐mm bismuth germanate and plastic scintillators. The sensitivity ratios of two scintillators with different elemental compositions can provide more information related to the energy of the incident photon, and scintillators with different thicknesses can provide a constant parameter which is necessary in the calculation of the beta‐ray and gamma‐ray counting fractions. A mixed source containing 60Co and 90Sr was used to estimate the accuracy of the proposed method. The gamma‐ray counting fraction was successfully deduced with a relative error of 2.01%. The method is expected to be used for cost‐effective assessment of radioactive waste resources and conservative estimation of the radioactivity of pure beta‐emitting radionuclides. A method for discriminating between the counting rates attributable to beta rays and gamma rays was proposed. The method was based on the characterization of the sensitivity ratios to gamma and beta rays for four scintillators: 10 and 20 mm, bismuth germanate and plastic scintillators. The fraction of the gamma‐ray counting rate using a combined 60Co and 90Sr source was successfully deduced with a relative error of 2.01%.